Mathematical Models of Athletic Performances
Wind and altitude effects in the short sprints: 100 m sprint Adjusted all-time rankings 200 m sprint 400 m sprint Mercier Scoring Tables: A method of cross-event/gender comparison other articles: Modeling curve running in the 200m Predicting the Future of Athletics Misc info: 100m Split Data